The mystery of Sacrae cantiones (Nuremberg 1597) - Gancarczyk, Paweł (De musica disserenda, 2007)
A copy of Sacrae cantiones, a collection of compositions by Jacob Handl - Gallus published in 1597 in Nuremberg, is preserved as a unicum in Gdańsk and in Warsaw. However, this is not a new edition but merely a copy of the fourth volume of the composer's Opus musicum, printed in Prague in 1590, with a changed title-page. The author presents arguments to show that the Sacrae cantiones were created on the initiative of Georg Handl, the composer's brother and printer, who in this way hoped to increase the chance of selling the rest of the examples of the Opus musicum that remained in stock after Jacob's death.
Keywords: Gallus, Jacobus, 1550-1591; Handl, Georg; glasbeno tiskarstvo